ETIKA KERJA ISLAM DAN KEADILAN ORGANISASI: STUDI PADA BMT DI KABUPATEN KUDUS - Rokhman, Wahibur (LP2M IAIN kUDUS, 2015)
WORK ETHICS OF ISLAM AND ORGANIZATIONAL JUSTICE: Study on a BMT in Kudus, This research aims to analyze the relationship of work ethics of Islam and organizational justice in BMT in Kudus. The organizational justice is measured using three dimensions of justice developed by Cropanzano et al. (2007), they are: distribution justice, procedural fairness and interactional justice. Further, the study also tested the influence of the three dimensions of justice against work ethics of Islam felt by employees. The results of this research show that the level of organizational justice and work ethics of Islam felt by employees working in the BMT in Holy is high enough. The results of the regression analysis also showed a significant positive influence on the distribution of Justice, procedural fairness and interactional justice against the work ethics of Islam. Implications, limitations and suggestions for the next research are also discussed in this article.keywords: Distribution Justice, Procedural Justice, Work Ethics Of Islam.Penelitian ini bertujuan untuk menganalisis hubungan etika kerja Islam dan keadilan organisasi di Baitul mal wat tamwil (BMT) di Kabupaten Kudus. Keadilan Organisasi disini diukur menggunakan tiga dimensi keadilan yang dikembangkan oleh Cropanzano dkk. (2007) yaitu: keadilan distribusi, keadilan prosedural dan keadilan interaksional. Lebih lanjut, penelitian ini juga menguji pengaruh tiga dimensi keadilan terhadap etika kerja Islam yang dirasakan oleh karyawan. Hasil penelitian ini menunjukkan bahwa tingkat keadilan organisasi dan etika kerja Islam yang dirasakan oleh karyawan yang bekerja di BMT di Kudus cukup tinggi. Hasil analisis regresi juga menunjukkan adanya pengaruh yang positif signifikan keadilan distribusi, keadilan prosedural dan keadilan interaksional terhadap etika kerja Islam. Implikasi, keterbatasan dan saran untuk penelitian yang akan datang juga dibahas dalam artikel ini.kata kunci: Keadilan Distribusi, Keadilan Prosedural, Etika Kerja Islam.